Effect of inoculation with symbiotic endo-and ectomycorrhizal fungi on physiological parameters of sweet cherry leaves - Герасько, Тетяна Володимирівна; Герасько, Татьяна Владимировна; Herasko, Tetiana; Pyda, Svitlana (My University, 2021)
EN : Sweet cherry (Pmnus avium L.) is the dominant fruit crop of our region. The relevance of our research is due to the need to develop a sustainable, independent of external resources organic technology for growing sweet cherry. Abandonment of synthetic mineral fertilizers and chemical plant protection products, inoculation of fmit tree roots with endo- and ectomycorrhizal fungi should to promote agroecosystem sustenability.
Keywords: organic technology for growing sweet cherry; synthetic mineral; protection products; inoculation; ectomycorrhizal fungi; agroecosystem; sweet cherry; leaves